The Influence Of Pandemic Educational Policy Implementation Toward Learning Effectiveness (Case Study at SMK NU Al-Farisi Tarogong Kaler Garut) - Erna Rustiana; Khilda Fauzi; Eka Setiawati Putri (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2022)
This study aims to determine the influence of pandemic educational policy implementation toward the effectiveness of learning at SMK NU Alfarisi Tarogong Kaler Garut. The method used on this study is the Pearson correlation research method because this analysis used a way of correlating each item's score with the total score. The data processing technique uses validity test, reliability test, simple regression analysis, correlation coefficient, and coefficient of determination assisted by SPSS 22 program. Hypothesis testing technique used t test. To determine the influence of pandemic educational policy implementation toward the effectiveness of learning then correlation coefficient test, determination test and hypothesis testing were carried out. Based on the results of the study, showing that the implementation of pandemic educational policy was not significantly influential on the effectiveness of learning by 14.1% while the remaining 85.9% was influenced by other factors which are not examined on this study. Calculation of the correlation coefficient between the implementation of pandemic educational policy and the effectiveness of learning was 37.6% ranging from 0.20-0.399. It means that the correlation between X variable (implementation of pandemic educational policy) to Y variable (learning effectiveness) is low and the hypothesis test is -2.223 while the t table is 2,042. The value proves that the value < which means that H0 is accepted and Ha is rejected meaning that the influence of educational policy implementation has no significant effect on the effectiveness of learning.